تقییم أثر تمویل المشروعات البحثیىة بجامعة جنوب الوادی على کمیة النشر العلمی ونوعیته - Doaa Elberry (المجلة الدولية لعلوم المكتبات والمعلومات)
Like most Egyptian universities, South Valley University (SVU) provides research project grants to their staff to publish Aquality research.However,no bibliometric study was undertaken to evaluate the output of these grants.The aim of this study was to measure the impact of research project funding on the scientific publication productivity and quality of SVU.The data of publications in 2013-2019 were collected from the higher studies and research sector of SVU and analyzed using bibliometric approach. The publication citation indices were obtained from Google Scholar. The Journal impact factors were retrieved from Journal citation reports of Clarivate analytics. Furthermore, the journals published papers from the grants were examined for Web of Science and Scopus indexing. The results shown that the SVU funded 80 projects in 2013-2019 by 1.790.000 Egyptian pounds.The total productivity was only 14 publications with 19 citations.The total costs per one publication and citation were 127.9 and 94.2 thousand respectively. Only three publications arose in WOS-indexed and Scopus journals with Impact factors and 11 publications went to non-indexed journals. The finding suggests that SVU-project grants has very low impact on research performance at SVU. The SVU’s research grants should be reoriented in a way to increase the quantity and quality of the researcher's publication at the SVU and subsequently improve the SVU international ranking. This is the first study to report the efficiency of Egyptian university grants on publication quantity and quality. This result will be instructive for the decision-makers at SVU. Similar studies should be applied in other Egyptian universities.